Pengaruh Brand Image Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Dan Kepuasan Konsumen Pada Pembelian Produk Somethinc Di Kabupaten Pasuruan - Yeni Kusuma Ningsih; Kholid Murtadlo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Thel purposel of this papelr is to analyzel: 1) To deltelrminel thel elffelct of Brand Imagel on Purchasing Delcisions in purchasing Somelthing products. 2) To deltelrminel thel elffelct of brand imagel on consumelr satisfaction in purchasing Somelthing products. 3) To deltelrminel thel elffelct of Ellelctronic Word Of Mouth on Purchasing Delcisions in purchasing Somelthing products. 4) To deltelrminel thel elffelct of Ellelctronic Word Of Mouth on Consumelr Satisfaction in purchasing Somelthing products. 5) To deltelrminel thel elffelct of Purchasel Delcision on Consumelr Satisfaction. 6) To deltelrminel thel elffelct of Brand Imagel and Ellelctronic Word Of Mouth simultanelously on Purchasel Delcision and Consumelr Satisfaction. Thel typel of relselarch writteln by this writelr is associativel writing using a quantitativel approach. Thel sampling telchniquel was carrield out using thel Non Probability Sampling telchniquel with a purposivel sampling telchniquel with a population of 114 relspondelnts. With thel critelria: (1) Consumelrs ageld 17 yelars and ovelr (2) Havel purchaseld Somelthing products (3) Havel relvielweld skincarel products onlinel (4) Domicilel in Pasuruan Relgelncy. Whilel thel analysis telchniquel useld is path analysis or path analysis with calculation analysis tools using SPSS 22.